The genus Sveltia (Gastropoda, Cancellariidae) in the Atlantic Pliocene of Iberia with a new species from the Cenozoic Mondego Basin of Portugal. (January 2022) - Landau, Bernard M.; Silva, Carlos Marques da
Abstract: The cancellarid genus Sveltia Jousseaume, 1887, is widespread in western European and North African Neogene marine fossil assemblages. In Pliocene deposits it is commonly represented by Sveltia varicosa (Brocchi, 1814 ), which until recently was considered a widely distributed taxon in the Mediterranean Sea and adjacent Atlantic faunas. A recent review of the species from the Pliocene of Italy and Spain (Guadalquivir Basin), leading to the erection of S . confusa, prompted the reassessment of the Sveltia material from the Atlantic Pliocene of the Portuguese Mondego Basin and the subsequent description of Sveltia sofiae n. sp. Consequently, a mosaic of species has emerged from what was previously viewed as the broad Atlanto-Mediterranean range of the widespread and quite variable S . varicosa . From a biogeographic standpoint, it is now clear that S . varicosa was a Mediterranean species, occurring east of the Alboran Sea. Sveltia confusa had a mainly Atlantic distribution, from the French Pliocene Ligerian Gulf to the Gulf of Cadiz, at least, and straddling the Strait of Gibraltar into the Alboran Sea. Sveltia sofiae n. sp. was endemic to western Iberia, represented today only in the western Portuguese Mondego Basin. Sveltia is a thermophilic genus. Since early Pliocene times, because of northeastern Atlantic sea surface temperature decline, it underwent a southward range contraction, occurring today—in the eastern Atlantic—from Cape Blanc, Mauritania, south. This range reduction was coupled with the post mid-Piacenzian southward contraction of the Pliocene Mediterranean-West African tropical molluscan province and the consequent rise of the present-day Mediterranean-Moroccan subtropical province. UUID: http://zoobank.org/0cf3c73a-8d57-472e-87e4-f1ad065e5fb6 .